PAGUYUBAN MINANG SEBAGAI JARING PENGAMAN SOSIAL DAN PENJAGA IDENTITAS KULTURAL DI ACEH BARAT - M. Farhan; Sopar Sinambela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of the Minangkabau Student Association (IMAMI) at Teuku Umar University as a social safety net and guardian of the cultural identity of the Minangkabau community in West Aceh. Using an ethnographic approach with participatory observation techniques, in-depth interviews, and documentation, the research was conducted during May-June 2026. The theories used include Robert D. Putnam's Social Capital, Emile Durkheim's Social Solidarity, and Stuart Hall's Cultural Identity. The results of the study show that IMAMI carries out three main functions: as a social safety net through trust, social networks, and social norms as a guardian of cultural identity, through the preservation of Minangkabau values, and as a cultural space that allows identity negotiation in the multicultural context of West Aceh. IMAMI is interpreted by its members as a 'second family' that provides a sense of security, solidarity, and the continuity of Minangkabau culture in a land of exile.Keywords: Put the keywords here